Hepatic hepcidin/intestinal HIF-2a axis maintains iron absorption during iron deficiency and overload - Schwartz, A; Das, N; Ramakrishnan, S; Jain, C; Jurkovic, M; Wu, J; Nemeth, E; Lakhal-Littleton, S; Colacino, J; Shah, Y (American Society for Clinical Investigation, 2018)
Iron-related disorders are among the most prevalent diseases worldwide. Systemic iron homeostasis requires hepcidin, a hepatic-derived hormone that controls iron mobilization through its molecular target, ferroportin (FPN), the only known mammalian iron exporter. This pathway is perturbed in diseases that cause iron overload. Additionally, intestinal HIF-2a is essential for the local absorptive response to systemic iron deficiency and iron overload. Our data demonstrate a hetero-tissue crosstalk mechanism, where liver hepcidin regulated intestinal HIF-2a in iron deficiency, anemia, and iron overload. We show that FPN controlled cell autonomous iron efflux to regulate the activity of iron-dependent, intestinal prolyl hydroxylase domain enzymes to stabilize HIF-2a. Pharmacological blockade of HIF-2a using a clinically relevant and highly specific inhibitor successfully treated iron overload in a mouse model. These findings demonstrate a molecular link between liver hepcidin and intestinal HIF-2a that controls physiological iron uptake and drives iron hyperabsorption during iron overload.